Respuesta :

it’s the last option

Answer:

The  correct application of the quadratic formula is:

               [tex]x=\dfrac{9\pm \sqrt{(-9)^2-4(6)(22)}}{2(6)}[/tex]

Step-by-step explanation:

The quadratic equation is given by:

[tex]y=6x^2-9x+22[/tex]

We know that the solution of the quadratic equation:

[tex]y=ax^2+bx+c[/tex]

is given by:

[tex]y=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

Here we have:

[tex]a=6[/tex]

[tex]b=-9[/tex]

and

[tex]c=22[/tex]

Hence, the quadratic formula is given by:

[tex]x=\dfrac{-(-9)\pm \sqrt{(-9)^2-4\cdot (6)\cdot (22)}}{2\cdot (6)}[/tex]

i.e.

[tex]x=\dfrac{9\pm \sqrt{(-9)^2-4(6)(22)}}{2(6)}[/tex]